Meta-Heurística Para Analise De Otimização Em Transporte Publico - Batista, Mariana Brito (Universidade Federal do Tocantins, 2022)
This work consist on the publication of the applied proposal of a problem of optimization of vehicle programming that aims to reduce costs in the use of buses and minibuses, vehicles used in Palmas - Tocantins for urban public use. To meet the city’s mobility demand, a company manages and provides this service. However, it has regularly increased the usage fee, either to adjust the value or to pass on the costs to the end user. However, these essential expenses for the performance of services, if optimized, could be lower without affecting the availability and effectiveness of public transport. It would be beneficial for the company that would disburse less for the maintenance of the activity and also for the population. When we talk about issues related to optimization, we put the test the metaheuristics, algorithms that work with a certain level of randomness, but that throughout the process seek to find the best possible solution. In a study carried out, we found a desired optimization margin so that supposedly an increase in the use tariff was not passed on to the population, in which the algorithm can establish the real possibility of implementing the optimization scheme of the fraction of vehicles used in public transport service of Palmas.